Enhanced Recovery After Surgery (ERAS) pada Pediatrik yang Menjalani Operasi Kolorektal - Pratomo, Bhirowo Yudo; Widyastuti, Yunita; Ilman, Pesiar (Jurnal Komplikasi Anestesi, 2021)
Enhanced recovery after surgery (ERAS) was first described by Henrik Kehlet as a tool for optimizing perioperative care. The general scope of ERAS includes perioperative counseling, limiting the fasting hours before surgery, postoperative enteral intake, early mobilization, use of non-opioid pain medications, and restriction of intravenous fluids, drainage, and catheters. Colorectal surgery in pediatrics has a higher infection rate in the surgical area than in adults, thereby the implementation of ERAS in this operation canhave a big impact. There are few studies on the implementation of ERAS in pediatrics. Despite that, the available data shows the implementation of ERAS in pediatrics undergoing colorectal surgery is positive.